Analysis of the knowledge of medical interns on the management of Exogenous Intoxications (Research, Society and Development, 2022)
Exogenous intoxication is caused by any external substance that harms the body, causing changes that result in the appearance of signs and symptoms the require urgente and ∕ or emergency care due to health risk, which requires effective, precise and effective interventions, short and medium term effectiveness. Poisoning is considered na importante public health problem that must be investigated with the consequent generation of information that will foster the capacity of countries to deal with this issue. This study aims to analyze the level of knowledge of medical internship students about the management of intoxicated patients. This is a cross-sectional, descriptive, and quantitative study with a basic and strategic purpose. It will be used as a data collection instrument, the application of questionnaire with clinical cases evaluating the knowledge of the interviewees. Thus, it is expected that it will be possible to appreciate their learning on the subject. In this sense, the study is significant, contributing to the population’s well-being with effective, precise and highly effective interventions.